The Relationship Between the Components of E-Government Services Towards Corruption in Malaysia and Indonesia - Purnamasari, Pupung; binti Amran, Noor Afza; Nu'man, A. Harits; Frendika, Rusman; Mohamad Nor, Mohamad Naimi; Ismail, Mohamad Sharofi (KnE Social Sciences, 2023)
This study investigates the correlation between the components of e-government services and corruption levels in Malaysia and Indonesia. Both countries have implemented various measures, including advanced e-government platforms and public participation, to combat corruption. However, instances of corruption have not shown a significant decline in either country. A total of 240 questionnaires were distributed to respondents from various sectors, including government, entrepreneurs, academia, non-governmental organizations (NGOs), and the media, in Indonesia and Malaysia. The Mann-Whitney U test was utilized to compare e-government services and corruption levels between the two countries. Interestingly, the results indicate variations in the e-government models adopted in Indonesia and Malaysia. In Malaysia, Government-to-Government (G2G) and Government-to-Citizen (G2C) interactions demonstrate a significant impact on corruption levels. In contrast, in Indonesia, Government-to-Business (G2B) and G2C interactions exhibit significant effects on corruption. Keywords: e-government, Government to Government (G2G), Government to Business (G2B), Government to Citizenship (G2C), anti-corruption